Legal Certainty in Regulating Vice Ministers’ Concurrent Positions: Implications of Constitutional Court Decision No. 128/PUU-XXIII/2025 for Executive Governance - Salahudin Pakaya; Moh. Fadli; Ismet Hadi (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
This article examines the legal certainty implications of Constitutional Court Decision No. 128/PUU-XXIII/2025, which extends the office incompatibility rule in Article 23 of Law No. 39 of 2008 on State Ministries to vice ministers. Using doctrinal legal research with statutory, case, conceptual, and comparative approaches, this article reconstructs the Court’s ratio decidendi and evaluates the ruling through four indicators of legal certainty: normative clarity, institutional coherence, predictability, and administrability. The analysis shows that the decision strengthens normative clarity by closing a statutory gap that previously allowed vice ministers to hold concurrent positions in state owned enterprises, private companies, or publicly funded organizations. Yet the ruling also creates implementation risks because the transitional period may invite fragmented compliance, administrative delay, or selective enforcement. This article argues that legal certainty after the decision depends not only on the Court’s interpretation, but also on concrete executive follow up. Its novelty lies in developing a compliance framework consisting of normative clarification, institutional mapping, transitional safeguards, and verifiable replacement mechanisms to align constitutional supremacy, executive accountability, and state owned enterprise governance.